Early adaptation strategies of Saccharomyces cerevisiae and Torulaspora delbrueckii to co-inoculation in high sugar grape must-like media. (September 2020) - Tondini, Federico; Onetto, Cristobal A.; Jiranek, Vladimir
Abstract: Torulaspora delbrueckii and Saccharomyces cerevisiae are yeast species found concurrently in wine. In order to commence fermentation, they adapt to the initial harsh environment, maintaining cellular homeostasis and promoting metabolism. These actions involve an intricate regulation of stress tolerance, growth and metabolic genes. Their phenotypes are influenced by the fermentation environment and physiological state of the cell, but such gene-environment interactions are poorly understood. This study aimed to compare the cell physiology of the two species, through genome-wide analysis of gene expression, coupling Oxford Nanopore MinION and Illumina Hiseq sequencing platforms. The early transcriptional responses to stress, nutrients and cell-to-cell communication were analysed. Particular attention was given to the fundamental gene modulations, leading to an understanding of the physiological changes needed to maintain cellular homeostasis, exit the quiescent state and establish dominance in the fermentation. Our findings suggest the existence of species-specific adaptation strategies in response to growth in a high sugar synthetic grape juice medium. Highlights: Species-specific adaptation strategies were observed in response to growth in high sugar synthetic grape juice medium. T. delbrueckii response relied on the broader activation of the environmental stress response. S. cerevisiae promoted growth and sugar consumption exhibiting strong glucose catabolite repression genes expression.